Introduction/Introduksiyon - Guillermo, Ramon; Benitez, Christian; Ong, Charlson; Evasco, Eugene (Likhaan: The Journal of Contemporary Philippine Literature; Vol 17 No 1 (2023): LIKHAAN 17: The Journal of Contemporary Philippine Literature, 2023)
A Likhaan issue is always something like a kaleidoscope.